Do attributes of persons with chronic kidney disease differ in low- and middle-income countries compared to high income countries? Evidence from population-based data in six countries - Anand, S; Zheng, Y; Montez-Rath, M; Jin, W; Perico, N; Carminati, S; Narayan, K; Tandon, N; Mohan, V; Jha, V; Zhang, L; Remuzzi, G; et al. (BMJ Publishing Group, 2017)
Kidney biopsies to elucidate cause of chronic kidney disease (CKD) are performed in a minority of persons with CKD living in high-income countries, since associated conditions—i.e., diabetes mellitus, vascular disease, or obesity with prediabetes, prehypertension, or dyslipidemia—can inform management targeted at slowing CKD progression in a majority. Attributes of CKD may differ in substantially, however, among persons living in low- and middle-income countries (LMICs). We used data from population or community-based studies from 5 LMICs (China, urban India, Moldova, Nepal, and Nigeria) to determine what proportion of persons with CKD living in diverse regions fit one of the three major clinical profiles, with data from the U.S. National Health Nutrition and Examination Survey as reference. In the U.S., urban India, and Moldova, 79.0-83.9%; in China and Nepal, 62.4-66.7%; and in Nigeria 51.6% persons with CKD fit one of three established risk profiles. Diabetes was most common in urban India and vascular disease in Moldova (50.7% and 33.2% of persons with CKD in urban India and Moldova respectively). In Nigeria, 17.8% of persons with CKD without established risk factors had albuminuria ≥ 300 mg/g, the highest proportion in any country. While a majority of persons with CKD in LMICs fit into one of three established risk profiles, the proportion of persons who have CKD without established risk factors is higher than in the U.S. These findings can inform tailored CKD detection and management systems, and highlight the importance of studying potential causes and outcomes of CKD without established risk factors in LMICs.